(untitled) (Jurnal Informatika dan Komputasi: Media Bahasan, Analisa dan Aplikasi, 2024)
Abstract Very rapidly technological advances allow for various efforts to provide convenience and comfort for humans, one of which is to make everything completely automated. Automatic door locks using RFID sensors based on Arduino Nano are door locks that open automatically by attaching a card to an RFID sensor (Radio frequency identification) as the input media. Automatic door locks have been widely used in daily life, however, in making automatic door locks require a large cost. In this thesis the author makes the design of a simple automatic door lock, this automatic door lock works by utilizing the Arduino nano microcontroller as a control system, RFID sensors as input media, solenoid as a key drive system and WEB API as a media user interface. The existence of this automatic door lock will provide benefits in human life, because it can facilitate the owner in maintaining the security of their home.